Transcriptomic Changes of Telencephalon and Hypothalamus in Largemouth Bass (Micropterus salmoides) Under Crowding Stress - Meijia Li; Leshan Yang; Ying Liu (Biology, 2025)
Crowding stress is an inevitable stressor in intensive farming, yet its underlying mechanisms are still obscure, severely hindering the aquaculture industry’s healthy development. As the primary sensory and regulatory organ for stressors, the brain plays a crucial role in stress responses. In this study, the effect of crowding stress on the telencephalon (Tel) and hypothalamus (Hy) has been explored using RNA sequencing. After four weeks of crowding stress, neuroinflammation-related genes were significantly induced in both the Tel and Hy. Additionally, cell fate-related processes were markedly altered. Neurogenesis-related pathways, including the Wnt and Hedgehog signaling pathways, were significantly enriched in both regions. The apoptosis-related genes (caspase3, p53) were predominantly downregulated in the Tel (log2Fold Change: −1.27 and −0.71, respectively), while ferroptosis-related genes (ho1, ncoa4) were specifically activated in the Hy (log2Fold Change: 1.15 and 0.73, respectively). The synaptic plasticity-related genes (prkcg, cacna1d) were significantly downregulated in both the Tel (log2Fold Change: −1.78 and −0.88) and Hy (log2Fold Change: −1.99 and −1.52). Furthermore, neurotransmitter synthesis (γ-aminobutyric acid (GABA) and serotonin (5-HT)) was disrupted in the Tel, whereas growth-related hormone gene expression was markedly altered in the Hy. These findings provide novel insights into the neurobiological mechanisms of chronic crowding stress in fish, laying a foundation for developing brain-targeted strategies to enhance welfare and mitigate stress in intensive largemouth bass farming.